Anti-hMAM Monoclonal Antibodies Evaluated in Breast and Non-Breast Tissues for Differential Diagnosis Implication. Issue 3 (May 2016) - Lv, Xiaojuan; Feng, Xiaoyan; Hao, Xiaopeng; Meng, Di; Yang, Xiqin; Xiu, Bingshui; Chen, Kun; Lu, Yinglin; Zhang, Heqiu; Zeng, Yanjun; Huang, Yan
Purpose: Human mammaglobin (hMAM) is a breast tissue-specific marker that may have potency for the diagnosis of breast cancer. However, there is a lack of commercialization of anti-hMAM antibody made in China. Methods: Immunoreactivities of 2 self-made monoclonal anti-hMAM antibodies, MEF521 and MDA822, were evaluated by immunohistochemistry staining and compared with imported monoclonal antibody ab81611. A total of 48 cases of primary breast cancers, 36 cases of benign or normal breast tissues, 52 cases of lymph nodes or organ metastases from breast cancer, and 90 cases of non-breast primary carcinoma tissues were analyzed. Results: All 3 anti-hMAM antibodies showed high positive expression of hMAM in primary breast cancers, benign, and normal breast tissues. The positive ratio for MEF521 (33.3%) or MDA822 (44.4%) was much higher than that of ab81611 (16.7%) in lymph node metastasis from breast cancer (p = 0.038). There was no correlation between hMAM expression and clinicopathologic features of breast cancer in the 3 groups of antibodies. In 90 cases of non-breast primary carcinoma tissues, no hMAM-positive ones were observed in the MEF521 or MDA822 group, but 48 (53.3%) in the ab81611 group were positive, indicating that breast tissue specificity of the 2 self-made anti-hMAM monoclonal antibodies much higher than that of ab81611 (p<0.001). Conclusions: Our results showed that MDA822 and MEF521 are more specific to breast cancer as measured by means of immunohistochemistry. Therefore, the 2 self-made anti-hMAM antibodies may have good prospects for clinical application in the differential diagnosis of breast tumor and breast cancer metastases.